Computational Aerodynamics Analysis of Non-Symmetric Multi-Element Wing in Ground Effect with Humpback Whale Flipper Tubercles - Benjamin Arrondeau; Zeeshan A. Rana (Fluids, 2020)
The humpback whale flipper tubercles have been shown to improve the aerodynamic coefficients of a wing, especially in stall conditions, where the flow is almost fully detached. In this work, these tubercles were implemented on a F1 front-wing geometry, very close to a Tyrrell wing. Numerical simulations were carried out employing the <semantics>k−ω</semantics> SST turbulence model and the overall effects of the tubercles on the flow behavior were analyzed. The optimal amplitude and number of tubercles was determined in this study for this front wing where an improvement of <semantics>22.6%</semantics> and <semantics>9.4%</semantics> is achieved, respectively, on the lift and the <semantics>L/D</semantics> ratio. On the main element, the stall was delayed by <semantics>167.7%</semantics>. On the flap, the flow is either fully detached, in the large circulation zone, or fully attached. Overall, in stall conditions, tubercles improve the downforce generation but at the cost of increased drag. Furthermore, as the tubercles are case-dependent, an optimal configuration for tubercles implementation also exists for any geometry.